A new stationary phase based on porous graphene for capillary gas chromatography. Issue 9 (12th July 2022) - Huang, Yanni; Chen, Jia; Fu, Gafang; Zhang, Chi; Qiu, Hongdeng
Abstract: This work reported the preparation and evaluation of a 2D porous graphene as the stationary phase for gas chromatography with high‐resolution performance from non‐polar to polar structural isomers. As a result, the dynamically coated porous graphene capillary column has a film thickness of about 16 μm. After aging treatment at different temperatures, the porous graphene capillary column exhibited high thermal stability up to 300°C. In addition, the porous graphene capillary column has good column repeatability and reproducibility. The retention time RSDs are 2.61–3.90% ( n = 3) during the days and 4.58–4.78% ( n = 3) column‐to‐column. This work demonstrates the advantageous separation performance of a good potential for the porous graphene as a new stationary phase for gas chromatography analysis.